Removal of copper ions from aqueous solution using waste mill scales - Ahmad Nazri, Nur Asyikin; Azis, Raba'ah Syahidah; Sulaiman, Syazana; Azuan, Nurul Ayuni; Shaari, Abdul Halim; Che Man, Hasfalina; Ismail, Ismayadi; Ibrahim, Idza Riati; Mohd Saiden, Norlaily (Trans Tech Publications, 2020)
The optimization of the Copper ions (Cu ions) adsorption from aqueous solution for inclusion in prolonged the milling time of the extracted iron oxides from waste mill scales has been investigated. Different milling times were used to reduce the size of the raw mill scale which are 24, 48 and 72 h. The three adsorbents were characterized using XRD, FESEM and VSM. Adsorbents that milled for 72 hours gave pure magnetite from the XRD results. FESEM images revealed that prolonged the milling time might reduced the particle sizes. Magnetic hysteresis revealed that all the samples having ferromagnetic behavior. Batch adsorption experiment had been carried out with the three adsorbents and as the results, adsorbents that milled with 72 hours shown highest removal of Cu ions with 95% removal efficiency.